The economic benefits of increased sugar-free chewing gum in China: a budget impact analysis - Shuo Du; Chunzi Zhang; Wenhui Wang; Jian Liu; Chao Yuan; Yizhen Yu; Qing Chang; Shanshan Zhang; Yan Si (BMC, 2021)
Abstract Background To analyze the potential cost savings in dental care associated with increased sugar-free gum (SFG) use among Chinese teenagers and adults. Methods The amount of SFG chewed per year and decayed, missing and filled teeth (DMFT) was collected from a cross-sectional survey to create a dose-response curve assumption. A cost analysis of dental restoration costs was carried out. A budget impact analysis was performed to model the decrease in DMFT and the subsequent cost savings for dental care. Three different scenarios for the increase in the number of SFG were calculated. Results The average cost savings per person in the Chinese population due to increasing SFG use ranged from 45.95 RMB (6.94 USD) per year to 67.41 RMB (10.19 USD) per year. It was estimated that 21.51-31.55 billion RMB (3.25-4.77 billion USD) could be saved annually if all SFG chewers among Chinese teenagers and adults chewed SFG regularly. Conclusion This study suggests that dental care costs could be significantly reduced if SFG use increased in the Chinese population.